Methionine-Functionalized Graphene Oxide/Sodium Alginate Bio-Polymer Nanocomposite Hydrogel Beads: Synthesis, Isotherm and Kinetic Studies for an Adsorptive Removal of Fluoroquinolone Antibiotics - Sushma Yadav; Anupama Asthana; Ajaya Kumar Singh; Rupa Chakraborty; S. Sree Vidya; Ambrish Singh; Sónia A. C. Carabineiro (Nanomaterials, 2021)
In spite of the growing demand for new antibiotics, in the recent years, the occurrence of fluoroquinolone antibiotics (as a curative agent for urinary tract disorders and respiratory problems) in wastewater have drawn immense attention. Traces of antibiotic left-overs are present in the water system, causing noxious impact on human health and ecological environments, being a global concern. Our present work aims at tackling the major challenge of toxicity caused by antibiotics. This study deals with the efficient adsorption of two commonly used fluoroquinolone (FQ) antibiotics, i.e., Ofloxacin (OFX) and Moxifloxacin (MOX) on spherical hydrogel beads generated from methionine‒functionalized graphene oxide/ sodium alginate polymer (abbreviated Met-GO/SA) from aqueous solutions. The composition, morphology and crystal phase of prepared adsorbents were characterized by X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), Fourier transform infrared spectroscopy (FTIR), high-resolution transmission electron microscopy (HR-TEM) and thermogravimetric analysis/differential thermogravimetry (TGA/DTG). Batch adsorption tests are followed to optimize the conditions required for adsorption process. Both functionalized and non-functionalized adsorbents were compared to understand the influence of several experimental parameters, such as, the solution pH, contact time, adsorbent dosage, temperature and initial concentration of OFX and MOX on adsorption. The obtained results indicated that the functionalized adsorbent (Met-GO/SA) showed a better adsorption efficiency when compared to non-functionalized (GO/SA) adsorbent. Further, the Langmuir isotherm was validated as the best fitting model to describe adsorption equilibrium and pseudo second-order-kinetic model fitted well for both types of adsorbate. The maximum adsorption capacities of Met-GO/SA were 4.11 mg/g for MOX and 3.43 mg/g for OFX. Thermodynamic parameters, i.e., ∆G°, ∆H° and ∆S° were also calculated. It was shown that the overall adsorption process was thermodynamically favorable, spontaneous and exothermic in nature. The adsorbents were successfully regenerated up to four cycles with 0.005 M NaCl solutions. Overall, our work showed that the novel Met-GO/SA nanocomposite could better contribute to the removal of MOX and OFX from the liquid media. The gel beads prepared have adequate features, such as simple handling, eco-friendliness and easy recovery. Hence, polymer gel beads are promising candidates as adsorbents for large-scale water remediation.